O Direito Desportivo enquanto uma disciplina autônoma - Fachada, Rafael Terreiro (2016)
The study of Science of Law requires of its scholars a duality that is characterized by respect for traditions and the need for improvement. Since there is society, there is somehow some kind of Law. Throughout the centuries, legal scholars have focused their studies not only on the material part, but on the existential and organizational genesis system presented as one when exposed through a macro look, but also subdivided into restricted looks. These subdivisions, on the other hand, cannot be looked as a natural and leak proof. In fact, they develop an eternal alignment with constant demands which arise within society. Every time a social demand becomes complex enough, which is verified by the requirements listed by the doctrine, we have a new autonomous subdivision, not an independent one. Each of these subsystems or subdivisions is called "discipline" or "branch". The present research will discuss if Sports Law is in compliance with the requirements which may insure its existence as an autonomous discipline